Case Report: Post-COVID-19 Vaccine Recurrence of Guillain–Barré Syndrome Following an Antecedent Parainfectious COVID-19–Related GBS - Bellucci, Margherita; Germano, Francesco; Grisanti, Stefano; Castellano, Chiara; Tazza, Francesco; Mobilia, Emanuela Maria; Visigalli, Davide; Novi, Giovanni; Massa, Federico; Rossi, Silvia; Durando, Paolo; Cabona, Corrado; et al. (Frontiers in Immunology, 2022)
Guillain–Barré syndrome (GBS) is an autoimmune neurological disorder often preceded by viral illnesses, or, more rarely, vaccinations. We report on a unique combination of post-COVID-19 vaccine GBS that occurred months after a para-infectious COVID-19-related GBS. Shortly after manifesting COVID-19 symptoms, a 57-year-old man developed diplopia, right-side facial weakness, and gait instability that, together with electrophysiology and cerebrospinal fluid examinations, led to a diagnosis of post-COVID-19 GBS. The involvement of cranial nerves and IgM seropositivity for ganglioside GD1b were noteworthy. COVID-19 pneumonia, flaccid tetraparesis and autonomic dysfunction prompted his admission to ICU. He recovered after therapy with intravenous immunoglobulins (IVIg). Six months later, GBS recurred shortly after the first dose of Pfizer/BioNTech vaccine. Again, GBS diagnosis was confirmed by cerebrospinal fluid and electrophysiology studies. IgM seropositivity extended to multiple gangliosides, namely for GM3/4, GD1a/b, and GT1b IgM. An IVIg course prompted complete recovery. This case adds to other previously reported observations suggesting a possible causal link between SARS-CoV-2 and GBS. Molecular mimicry and anti-idiotype antibodies might be the underlying mechanisms. Future COVID-19 vaccinations/revaccinations in patients with previous para-/post-COVID-19 GBS, especially whether seropositive for ganglioside antibodies, deserves a reappraisal.